Agenda for meeting on 29 June 1938
043-0065-001 SPANISH MEDICAL AID COMMITTEE. 24, New Oxford Street, W.C.1. A meeting of the Committee will be held on Wednesday next June 29th., at 8.45pm. AGENDA. 1. Minutes of previous meeting 2. Matters arising therefrom 3. Special correspondence 4. Report of Organising Sub-Committee 5. Report of Personnel and Technical Sub-Committee 6. Further consideration of the position at Ucles 7. Any other business The Organising Sub-Committee of which you are a member will meet at 7pm on the same day. 292/946/43/65